Evaluation of control methods for thermal roll forming of aerospace composite materials - Land, Patrick; De Sousa, Luis; Ratchev, Svetan; Branson, David T.; Brookes, Harvey; Wright, Jon (SAE International, 2016)
With increased demand for composite materials in the aerospace sector there is a requirement for the development of manufacturing processes that enable larger and more complex geometries, whilst ensuring that the functionality and specific properties of the component are maintained. To achieve this, methods such as thermal roll forming are being considered. This method is relatively new to composite forming in the aerospace field, and as such there are currently issues with the formation of part defects during manufacture. Previous work has shown that precise control of the force applied to the composite surface during forming has the potential to prevent the formation of wrinkle defects. In this paper the development of various control strategies that can robustly adapt to different complex geometries are presented and compared within simulated and small scale experimental environments, on varying surface profiles. Results have found that traditional PID control can be utilized, although its robustness under varying conditions reduces performance in situations that are far from the tuned scenario. This causes the PID controller to struggle with geometries containing surfaces with high frequency surface variations. To enable more robust control an H∞ based controller was therefore developed for the thermal roll forming process. Simulated results show that while the individual implementation of both controllers were successful in achieving the desired response, the H∞ based controller was able to perform better across a wider range of desired surface profiles.